2019
DOI: 10.3390/jcm8071047
|View full text |Cite
|
Sign up to set email alerts
|

Neural Processing of Disorder-Related Stimuli in Patients with Anorexia Nervosa: A Narrative Review of Brain Imaging Studies

Abstract: Abnormalities and alterations in brain function are commonly associated with the etiology and maintenance of anorexia nervosa (AN). Different symptom categories of AN have been correlated with distinct neurobiological patterns in previous studies. The aim of this literature review is to provide a narrative overview of the investigations into neural correlates of disorder-specific stimuli in patients with AN. Although findings vary across studies, a summary of neuroimaging results according to stimulus category… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 129 publications
(164 reference statements)
3
20
0
1
Order By: Relevance
“…Further, it remains unclear how treatment-related changes in DMN activation during DD might be related to the observed clinical improvements as no correlations were found. As previously implied by Decker et al [16], however, the lack of correlation between the measures of DD and the clinical variables might be partially attributable to the monetary rewards used in our paradigm and future research, including disorder-relevant stimuli [64], which might be more informative in this respect [12]. Last but not the least, differentiating between state and trait effects is one of the challenges in AN research.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Further, it remains unclear how treatment-related changes in DMN activation during DD might be related to the observed clinical improvements as no correlations were found. As previously implied by Decker et al [16], however, the lack of correlation between the measures of DD and the clinical variables might be partially attributable to the monetary rewards used in our paradigm and future research, including disorder-relevant stimuli [64], which might be more informative in this respect [12]. Last but not the least, differentiating between state and trait effects is one of the challenges in AN research.…”
Section: Discussionmentioning
confidence: 74%
“…Importantly, however, the fMRI analysis targeting brain regions involved in executive decision-making (regessor 1) revealed less deactivation in the core nodes of the "task-negative" DMN at follow-up relative to baseline (TP2 > TP1). This finding is relevant not only to the literature on reward-based decision-making (including DD) in AN [7,60,61], but also to the greater functional neuroimaging literature in the disorder [10,[62][63][64], for at least three reasons. First, the "task-negative" DMN regions in which longitudinal changes were observed (medial prefrontal cortex, posterior cingulate/precuneus, inferior parietal lobule) highly overlapped those in which we previously found abnormally decreased activation (i.e., greater deactivation) in acAN-T1, in comparison to HC, using the same analysis [40].…”
Section: Discussionmentioning
confidence: 86%
“…The inferior temporal gyrus as part of the ventral visual stream is involved in higher-order object processing 55 . Multiple fMRI studies have revelaed alterations in this pathway both at rest and during visual presentation of face, food or body stimuli in adult AN and individuals with body dysmorphic disorder 34,[56][57][58][59][60][61][62] . Interestingly, the infertior temporal gyrus also shows similar alteration in fALFF values in individuals with autism spectrum disorder 63 , who share deficits in social cognition 64,65 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the design and the results differed between the included studies. Three further reviews confirmed these inconsistencies ( 6 8 ) and therefore conclusions remain questionable. None of the studies were confirmed by replication, so the reported findings should not yet be regarded as established scientific knowledge.…”
Section: Introductionmentioning
confidence: 99%